Where do they all belong? Teaching math for belonging - Jaworski, Dan; Walker, Janet (Ohio Journal of School Mathematics, 2023)
This paper presents an inquiry project by Danny, a high school mathematics teacher from Israel, who aimed to build a sense of belonging in at-risk youth by connecting the mathematics curriculum to the students’ lives and interests. The project focused on improving students’ performance on the matriculation exam through the three types of belonging: formal, social, and cognitive. An example of a Desmos activity is presented to illustrate the potential of inquiry projects to build cognitive belonging in at-risk youth.